METODE PENDIDIKAN DASAR RASULULLAH SAW (STUDI ANALISIS HADIS-HADIS PENDIDIKAN DALAM KITAB SHAHIH BUKHARI) - Saragih, Muhari Syahlaili; Saragih, Lisna Syaheni Br (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2024)
The phenomenon of moral decadence, moral deterioration and erosion of students' faith as the next generation in the present day is increasingly concerning. Because the educational methods taught at this time tend to be different from the educational methods taught by the Prophet saw. So it raises a question: “What is the relevance between the educational methods of the Prophet saw and the educational methods today?”. The purpose of this study is to find out the educational methods used by the Prophet saw contained in the book of Shahih Bukhari, the effects resulting from the educational methods of the Prophet saw and the relevance of the educational methods of the Prophet saw to the current educational methods. This research can be classified as qualitative, a type of library research research. That is a literature study that focuses more on discussing the educational methods of the Prophet Muhammad saw through book literature, both primary and secondary data sources. Meanwhile, the main focus is to find educational values in the book of Shahih Bukhari. The results of this study show that there are so many educational methods in the book of Shahih Bukhari. The educational methods include: exemplary method, gentle/affectionate method, deductive method, parable method, figurative method, facilitation method, comparison method, question and answer method, repetition method, demonstration method, experiment method, problem-solving method, discussion method, praise / joy method, punishment method can be carried out by educators in instilling values in the affective realm and developing a mindset in the realm cognitive and commendable behavior exercises in the psychomotor realm. Both in the form of motivation and behavior of educators in providing educational methods to students by imitating the educational methods of the Prophet saw. The conclusion of the study emphasizes that the educational method of the Prophet saw is a method that has Islamic educational values and these educational values are in accordance with the demands of the Qur'an and hadith so that it is very important to be instilled in today's students. Basically, with the values of Islamic education, it is also what leads students to become the future generation of the nation who go from barbaric to civilized, have noble morals in social media and social society and are useful for the nation and religion.